RNAi-mediated gene silencing of lanosterol 14α- demethylase (ERG11)-encoding gene in ganoderma boninense - Lim, Fook Hwa (2022)
Oil palm basal stem rot (BSR) disease is caused by several species of Ganoderma including Ganoderma boninense. Available molecular tools for G. boninense are essential for providing the knowledge on the fungal infection process in oil palm. The objectives of this study are to isolate the full-length cDNA encoding Lanosterol 14α-demethylase (GbERG11) from G. boninense, to optimize a polyethylene glycol (PEG)-mediated protoplast transformation protocol for G. boninense, to perform the GbERG11 gene functional study via RNAi-mediated gene silencing approach and to transform the hpRNA-GbERG11 vectors into oil palm. A full-length 1980 bp cDNA encoding GbERG11 was successfully isolated and the GbERG11 shared high similarity (91%) to ERG11 from other basidiomycete fungi. Southern blot and genome data analyses indicated that there is only a single copy of GbERG11 gene in the G. boninense genome. An average concentration of 107/ml viable protoplasts were successfully isolated from G. boninense mycelium. The G. boninense PEGmediated protoplast transformation using 1 μg of transformation vector, 25% of PEG solution, 10 min of pre-transformation incubation and 30 min of posttransformation incubation has improved the transformation efficiency by 33.5 folds on average. Three hpRNA vectors corresponding to different regions of GbERG11 were prepared using the in vitro recombination between the entry vectors (containing different target regions of GbERG11) and hpRNA vector, pH7GWIWG2(I). The G. boninense transformed with the hpRNA vectors have shown reduced growth, expression of ERG11 and ergosterol content as much as 57.3%, 32.9% and 42.9%, respectively as compared to the PER71 (wild type). Less severe infection symptoms were observed on oil palm plantlets inoculated with G. boninense transformants as compared to the G. boninense PER71 (wild type) in the initial stages of in vitro inoculation study. Besides that, particle bombardment of oil palm calli with the hpRNA vectors (GbERG11) was performed. The selection process has led to regeneration of 8 putative transgenic greenish polyembryoids. As a conclusion, a gene function study for G. boninense has been successfully developed by using the PEG-mediated protoplast transformation and RNAi-mediated gene silencing approaches. Reduced GbERG11 gene expression followed by reduced ergosterol content was observed in the G. boninense transformants indicating the functional of this molecular tool. The G. boninense transformants have showed reduced pathogenicity towards oil palm at the initial stages of the in vitro inoculation study, which could highlight the GbERG11 gene role at the initial stage of infection. The developed molecular tools in this study can be applied for studying other genes in G. boninense, as well as other Ganoderma species or basidiomycete fungi. The putative transgenic oil palm plantlets can be further evaluated especially on the resistance against G. boninense, which could indicate the potential application of RNAi-mediated gene silencing in protecting oil palm against the Ganoderma infection.